2003
DOI: 10.1046/j.1460-9568.2003.02918.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxic lesions of the tegmental pedunculopontine nucleus impair copulation in naive male rats and block the rewarding effects of copulation in experienced male rats

Abstract: The tegmental pedunculopontine nucleus (TPP) of the brainstem mediates food reward in food-sated animals and opiate reward in drug-naive animals. In the present study, we examine the effect of excitotoxic lesions of the TPP on sexual behaviour in naive and experienced male rats. Male, Long-Evans rats received either 0.25 micro L injections of NMDA (4.2 micro g/side) or vehicle (shams) into the TPP. In sexually naive males, complete bilateral TPP lesions decreased all measure of copulation (i.e. mounts, intromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 79 publications
2
23
0
Order By: Relevance
“…Previous studies have shown that integrity of PPTg is necessary for arousal, attention, motivation and learning, and, particularly interestingly here, stimulus-reward associations (Steckler et al, 1994b). Studies using a variety of conditioning tasks have suggested a role for PPTg in assigning task-specific salience value to cue signals (Inglis et al, 1994(Inglis et al, , 2000Florio et al, 1999;Kippin and van der Kooy, 2003). Consistent with this idea, some PPTg cells in cat were found to respond to conditioned stimuli in a context-dependent way, failing to respond to the same cue when another signal indicated a different task requirement (Dormont et al, 1998).…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have shown that integrity of PPTg is necessary for arousal, attention, motivation and learning, and, particularly interestingly here, stimulus-reward associations (Steckler et al, 1994b). Studies using a variety of conditioning tasks have suggested a role for PPTg in assigning task-specific salience value to cue signals (Inglis et al, 1994(Inglis et al, , 2000Florio et al, 1999;Kippin and van der Kooy, 2003). Consistent with this idea, some PPTg cells in cat were found to respond to conditioned stimuli in a context-dependent way, failing to respond to the same cue when another signal indicated a different task requirement (Dormont et al, 1998).…”
Section: Discussionmentioning
confidence: 78%
“…GDP (final concentration, 1 M) was added to 100-g membranes from HEK cells or striata of wild-type, D1 mutant mice (22), or D2 mutant mice (23), and the assay mixture was incubated on ice for 10 min. The mixture was moved to 30°C and then incubated for 5 min before adding [ 35 S]GTP␥S (1,250 Ci/mmol) (PerkinElmer, Wellesley, MA) to a final concentration of 2.5 nM.…”
Section: Gtp␥s Assay Agonist-mediated [mentioning
confidence: 99%
“…It is particularly important to ascertain the mechanisms underlying progestins actions for mediating reinforcing behaviors, given the potential role of progesterone in mediating response to drugs of abuse (Frye, submitted for publication). Furthermore, given that neuronal adaptations in the ventral tegmental area have been proposed to account for the progressive transition from non-dependence to drug dependence, model systems such as this (Kippin and van der Kooy, 2003) are particularly valuable as they are free from potential confounds of direct drug-related effects and can be used to examine neural substrates for particularly salient motivated behaviors (Berridge and Robinson, 1998;Koob and Le Moal, 2001;Spanagel et al, 1993).…”
Section: Introductionmentioning
confidence: 99%